Patients transition: what is it like in the intensive care unit? discover the hidden realities from nurses’ perspective - Mohamed Ludin, Salizar; Arbon, Paul; Parker, Steve (2011)
Providing support for critically ill patients throughout their transition(s) while in the Intensive Care Unit (ICU) and following transfer is an important element of the nursing process during hospitalisation for critical illness. Because nurses are the primary caregivers in critical care contexts, understanding of patients’ transition experience is important and can facilitate better nursing care. To date, apart from the associated discussion of discharge planning issues, little is known about nurses’ understanding of the critically ill patients and their families’ experience. Thus this paper presents what it’s like for the patients and their families to be in transition in the Malaysian ICU. An interpretive descriptive research approach was used to describe transition experiences and followed by interpretation of findings from an ethnographic stance. Focus group (n=25), and in-depth individual interviews (n=10) were conducted sequentially in four Malaysian tertiary hospitals (7 ICUs) within a seven month period, in 2008. Data were subjected to qualitative thematic analysis. The findings were categorized into patients’ and families’ experience and seen as transition of location, health and illness, skill and care, knowledge need, hope and faith, and coping. In conclusion, the findings demonstrate the breadth of transition concerning the patients’ and families’ experiences and the journey of care in ICU. The major implication of this study is to understand that the critically ill patients’ transition experience is complex and extends beyond simple concerns of discharge planning and after care which have been previously the clinical focus of health organizations and care plans due to the impact to the society.